h y Philip Muehlenbeck. - Muehlenbeck, Philip; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
This book explores Czechoslovakia's diplomatic relations with African states and places them within a wider Cold War historiography, providing contextual background information on the evolution of communist Czechoslovakia's pro-Soviet foreign policy orientation. This shift in Soviet foreign policy made Africa a priority for the Soviet bloc.
Keywords: Political science; History, Modern; Africa -- History; Europe -- History; World politics; International relations; Political Science and International Relations; International Relations; Political History; African History; European History; Modern History; Electronic books